If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30.5 = -9.5 + 6(f + -8) Reorder the terms: 30.5 = -9.5 + 6(-8 + f) 30.5 = -9.5 + (-8 * 6 + f * 6) 30.5 = -9.5 + (-48 + 6f) Combine like terms: -9.5 + -48 = -57.5 30.5 = -57.5 + 6f Solving 30.5 = -57.5 + 6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6f' to each side of the equation. 30.5 + -6f = -57.5 + 6f + -6f Combine like terms: 6f + -6f = 0 30.5 + -6f = -57.5 + 0 30.5 + -6f = -57.5 Add '-30.5' to each side of the equation. 30.5 + -30.5 + -6f = -57.5 + -30.5 Combine like terms: 30.5 + -30.5 = 0.0 0.0 + -6f = -57.5 + -30.5 -6f = -57.5 + -30.5 Combine like terms: -57.5 + -30.5 = -88 -6f = -88 Divide each side by '-6'. f = 14.66666667 Simplifying f = 14.66666667
| -6[k-(2k+8)+6]=2(k+2) | | 180=12x+2+12x-4+12x-3 | | 4x+(x-5)=180 | | r/84=32.5/182 | | 4-19=17 | | 4+6(7c+7)= | | 4+9=57 | | c+24=36 | | 20.5=-2(3r+7) | | 2*0.166666666=a | | c+28=17 | | 7+3z=13 | | 11x^2+106x+63=0 | | -5-6.5(1+9.5x)=-26.5 | | 1.3(8-b)+3.7=-52 | | 2.4x-11.3=3.7-.6x | | 8=2x+m | | 1-15s=2(1-s) | | 2n-11=47 | | 6+6+6=3x | | x^3-32x+35=0 | | 1.05s-0.01(584.8-s)=28.26s | | 1/4(x-7)=2(3x+12) | | 3x=-5y+15 | | n-8=25 | | 8[8-(-2x-7)]=112x+456 | | (-6x^5y)(-2x^12y^4)=0 | | -28.5=4.5a-4a | | 10k^2-61k+6=0 | | (7x+3)(x-6)=0 | | 11(9c-1)-4=97c+11 | | 5*0.166666666=a |